2021
DOI: 10.1038/s41598-021-85281-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbial communities in wheat tissues and rhizosphere soil caused by dwarf bunt of wheat

Abstract: Dwarf bunt of wheat, which is caused by Tilletia controversa J.G. Kühn, is a soil-borne disease which may lead up to an 80% loss of yield together with degradation of the quality of the wheat flour by production of a fishy smell. In this study, high-throughput sequencing technology was employed to characterize the microbial composition of wheat tissues (roots, spikes, first stem under the ear, and stem base) and rhizosphere soil of wheat varieties that are resistant and susceptible to T. controversa. We observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Inoculant-induced modulation of wheat indigenous actinobacterial populations was previously demonstrated using a mixed consortium as inoculum, where endophytic actinobacterial populations, including Curtobacterium and Terrabacter , were reduced by half ( Conn and Franco, 2004 ). A similar trend was recently observed in resistant and susceptible wheat lines inoculated with the fungal pathogen Tilletia controversa , where the relative abundances of Microbacterium and Curtobacterium , among other actinobacterial genera, were differentially modulated ( Xu et al, 2021 ). Inoculant-induced increase in the relative abundance of the genus Brevibacterium , observed in this study, has been demonstrated both through the addition of inoculants in compost and in healthy rhizospheric soils compared with diseased ones ( Lee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 81%
“…Inoculant-induced modulation of wheat indigenous actinobacterial populations was previously demonstrated using a mixed consortium as inoculum, where endophytic actinobacterial populations, including Curtobacterium and Terrabacter , were reduced by half ( Conn and Franco, 2004 ). A similar trend was recently observed in resistant and susceptible wheat lines inoculated with the fungal pathogen Tilletia controversa , where the relative abundances of Microbacterium and Curtobacterium , among other actinobacterial genera, were differentially modulated ( Xu et al, 2021 ). Inoculant-induced increase in the relative abundance of the genus Brevibacterium , observed in this study, has been demonstrated both through the addition of inoculants in compost and in healthy rhizospheric soils compared with diseased ones ( Lee et al, 2021 ).…”
Section: Discussionsupporting
confidence: 81%
“…Further, Chryseobacterium and Massilia , and Nocardioides and Pseudomonas were abundant in wheat dwarf blunt infected resistant and susceptible varieties, respectively. Curtobacterium , Planococcus , Pantoea , and Exiguobacterium showed dominance in both resistant and susceptible varieties ( Xu et al, 2021 ). The phyllospheric microorganisms can tolerate extreme temperatures as well as substantial UV radiations, so they are a class of extremophiles.…”
Section: Overview Of the Wheat Microbiomementioning
confidence: 99%
“…These two classes of fungi exist in a variety of soils with resistance to pathogen infection (X. T. Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These two classes of fungi exist in a variety of soils with resistance to pathogen infection (X. Liu et al, 2021 ; T. Xu et al, 2021 ). Many genera of the class Mortierellomycetes belong to plant growth-promoting fungi (PGPF), which play a positive role in plant resistance to pathogen invasion ( Ozimek and Hanaka, 2021 ).…”
Section: Discussionmentioning
confidence: 99%